Stroke in Young Age - Study of 50 Cases - Miah, Md Titu; Hoque, AKM Aminul; Tarafder, Binoy Krishna; Romel, Syed Mohammad Ali; Hassan, Md Kamrul (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Stroke in young age is relatively uncommon but has serious impact on the affected family as well as society. The causes are more diversed and differ as compared to the elderly. Overall prognosis is better than elderly but there is still significant morbidity and mortality. We studied consecutive 50 stroke patients between the age of 15-45 admitted in Mymensingh Medical College Hospital. The objective of this study was to evaluate the aetiological pattern, associated risk factors and inpatient outcome. Mean age of the patients was 35.8 Â± 7.39 SD ( years ), female male ratio was 1 : 1.27. Infarction was found in 60% cases. Haemorrhage was in 40% cases. Dyslipidaemia was mostly associated risk factor in both infarction (83.3%) and in haemorrhage (75%). In 74% cases aetiology could not be identified. High prevalence of dyslipidemia as associated risk factor may indicate premature atherosclerosis. Overall in-patient mortality was12% .Mortality in haemorrhagic strokes is higher. Â  DOI = 10.3329/jom.v9i1.1419 J MEDICINE 2008; 9 : 10-15